Syntheses, structures, and stabilities of aliphatic and aromatic fluorous iodine(I) and iodine(III) compounds: the role of iodine Lewis basicity - Mukherjee, Tathagata; Biswas, Soumik; Ehnbom, Andreas; Ghosh, Subrata K.; El-Zoghbi, Ibrahim; Bhuvanesh, Nattamai; Bazzi, Hassan S.; Gladysz, John A. (Beilstein Journal of Organic Chemistry, 2017)
The title molecules are sought in connection with various synthetic applications. The aliphatic fluorous alcohols RfnCH2OH (Rfn = CF3(CF2)n–1; n = 11, 13, 15) are converted to the triflates RfnCH2OTf (Tf2O, pyridine; 22–61%) and then to RfnCH2I (NaI, acetone; 58–69%). Subsequent reactions with NaOCl/HCl give iodine(III) dichlorides RfnCH2ICl2 (n = 11, 13; 33–81%), which slowly evolve Cl2. The ethereal fluorous alcohols CF3CF2CF2O(CF(CF3)CF2O)xCF(CF3)CH2OH (x = 2–5) are similarly converted to triflates and then to iodides, but efforts to generate the corresponding dichlorides fail. Substrates lacking a methylene group, RfnI, are also inert, but additions of TMSCl to bis(trifluoroacetates) RfnI(OCOCF3)2 appear to generate RfnICl2, which rapidly evolve Cl2. The aromatic fluorous iodides 1,3-Rf6C6H4I, 1,4-Rf6C6H4I, and 1,3-Rf10C6H4I are prepared from the corresponding diiodides, copper, and RfnI (110–130 °C, 50–60%), and afford quite stable RfnC6H4ICl2 species upon reaction with NaOCl/HCl (80–89%). Iodinations of 1,3-(Rf6)2C6H4 and 1,3-(Rf8CH2CH2)2C6H4 (NIS or I2/H5IO6) give 1,3,5-(Rf6)2C6H3I and 1,2,4-(Rf8CH2CH2)2C6H3I (77–93%). The former, the crystal structure of which is determined, reacts with Cl2 to give a 75:25 ArICl2/ArI mixture, but partial Cl2 evolution occurs upon work-up. The latter gives the easily isolated dichloride 1,2,4-(Rf8CH2CH2)2C6H3ICl2 (89%). The relative thermodynamic ease of dichlorination of these and other iodine(I) compounds is probed by DFT calculations.
Keywords: chlorination; copper mediated perfluoroalkylation; crystal structure; DFT calculations; fluorous; hypervalent iodine; nucleophilic substitution; polar space group

Handbook of Fluorous Chemistry - Gladysz, J. A.; Curran, D. P.; Horváth, I. T. (Wiley-VCH, 2004)

Fluorous, Chemistry. Topics in Current Chemistry - Horváth, I. T. (Springer, 2012)

(untitled) - Mukherjee, T.; Gladysz, J. A. (Aldrichimica Acta, 2015)

(untitled) - Kysilka, O.; Rybáčková, M.; Skalický, M.; Kvíčalová, M.; Cvačka, J.; Kvíčala, J. (Collect. Czech. Chem. Commun., 2008)

(untitled) - Lapčik, J.; Girnello, O.; Ladmiral, V.; Friesen, C. M.; Ameduri, B. (Polym. Chem., 2015)

(untitled) - Dolbier, W. R., Jr (Chem. Rev., 1996)

(untitled) - Brace, N. O. (J. Fluorine Chem., 2001)

(untitled) - Cowell, A. B.; Tamborski, C. (J. Fluorine Chem., 1981)

(untitled) - Darses, S.; Pucheault, M.; Genêt, J.-P. (Eur. J. Org. Chem., 2001)

(untitled) - Miura, T.; Nakashima, K.; Tada, N.; Itoh, A. (Chem. Commun., 2011)

(untitled) - Jiang, D.-F.; Liu, C.; Guo, Y.; Xiao, J.-C.; Chen, Q.-Y. (Eur. J. Org. Chem., 2014)

(untitled) - Alvey, L. J.; Rutherford, D.; Juliette, J. J. J.; Gladysz, J. A. (J. Org. Chem., 1998)

(untitled) - Alvey, L. J.; Meier, R.; Soós, T.; Bernatis, P.; Gladysz, J. A. (Eur. J. Inorg. Chem., 2000)

(untitled) - Wende, M.; Seidel, F.; Gladysz, J. A. (J. Fluorine Chem., 2003)

(untitled) - Rocaboy, C.; Gladysz, J. A. (Chem. – Eur. J., 2003)

(untitled) - Podgoršek, A.; Jurisch, M.; Stavber, S.; Zupan, M.; Iskra, J.; Gladysz, J. A. (J. Org. Chem., 2009)

(untitled) - Tesevic, V.; Gladysz, J. A. (Green Chem., 2005)

(untitled) - Tesevic, V.; Gladysz, J. A. (J. Org. Chem., 2006)

(untitled) - Bravo, P., III; Montanari, V.; Resnati, G.; DeMarteau, D. D. (J. Org. Chem., 1994)

(untitled) - Lion, C. J.; Vasselin, D. A.; Schwalbe, C. H.; Matthews, C. S.; Stevens, M. F. G.; Westwell, A. D. (Org. Biomol. Chem., 2005)

(untitled) - Zagulyaeva, A. A.; Yusubov, M. S.; Zhdankin, V. V. (J. Org. Chem., 2010)

(untitled) - Cossairt, B. M.; Cummins, C. C. (New J. Chem., 2010)

(untitled) - Banks, D. F.; Huyser, E. S.; Kleinberg, J. (J. Org. Chem., 1964)

(untitled) - Tanner, D. D.; van Bostelen, P. B. (J. Org. Chem., 1967)

Handbook of Green Chemistry - Gladysz, J. A. (Catalysis Involving Fluorous Phases: Fundamentals and Directions for Greener Methodologies, 2009)

(untitled) - Kiss, L. E.; Kövesdi, I.; Rábai, J. (J. Fluorine Chem., 2001)

(untitled) - Rocaboy, C.; Rutherford, D.; Bennett, B. L.; Gladysz, J. A. (J. Phys. Org. Chem., 2000)

(untitled) - Friedrich, K.; Amann, W.; Fritz, H. (Chem. Ber., 1978)

(untitled) - Exner, O. (Correlation Analysis in Chemistry, 1978)

(untitled) - Maul, J. J.; Ostrowski, P. J.; Ublacker, G. A.; Linclau, B.; Curran, D. P. (Top. Curr. Chem., 1999)

(untitled) - Tesevic, V.; Gladysz, J. A. (Top. Organomet. Chem., 2008)

Handbook of Fluorous Chemistry - Gladysz, J. A.; Emnet, C. (Fluorous Solvents and Related Media, 2004)

(untitled) - Zhao, X.-F.; Zhang, C. (Synthesis, 2007)

Hypervalent Iodine Chemistry: Preparation, Structure, and Synthetic Applications of Polyvalent Iodine Compounds - Zhdankin, V. V. (John Wiley & Sons, 2014)

(untitled) - Hu, X. C.; Andrews, D. Q.; Lindstrom, A. B.; Bruton, T. A.; Schaider, L. A.; Grandjean, P.; Lohmann, R.; Carignan, C. C.; Blum, A.; Balan, S. A.; Higgins, C. P.; Sunderland, E. M. (Environ. Sci. Technol. Lett., 2016)
See for recent lead references.

(untitled) - Lo, A. S. W.; Horváth, I. T. (Green Chem., 2015)

(untitled) - Chu, Q.; Henry, C.; Curran, D. P. (Org. Lett., 2008)

(untitled) - Skalický, M.; Skalická, V.; Paterová, J.; Rybáčková, M.; Kvíčalová, M.; Cvačka, J.; Březinová, A.; Kvíčala, J. (Organometallics, 2012)

(untitled) - Minkwitz, R.; Berkei, M. (Inorg. Chem., 1999)

(untitled) - Rocaboy, C.; Hampel, F.; Gladysz, J. A. (J. Org. Chem., 2002)

(untitled) - McLoughlin, V. C. R.; Thrower, J. (Tetrahedron, 1969)

(untitled) - Ishihara, K.; Kondo, S.; Yamamoto, H. (Synlett, 2001)

(untitled) - van den Broeke, J.; Deelman, B.-J.; van Koten, G. (Tetrahedron Lett., 2001)

(untitled) - Ghosh, S. K.; Ojeda, A. S.; Guerrero-Leal, J.; Bhuvanesh, N.; Gladysz, J. A. (Inorg. Chem., 2013)

(untitled) - Su, H.-L.; Balogh, J.; Al-Hashimi, M.; Seapy, D. G.; Bazzi, H. S.; Gladysz, J. A. (Org. Biomol. Chem., 2016)

(untitled) - Guillevic, M.-A.; Arif, A. M.; Gladysz, J. A.; Horváth, I. T. (Angew. Chem., Int. Ed. Engl., 1997)

(untitled) - Montanari, V.; DesMarteau, D. D.; Pennington, W. T. (J. Mol. Struct., 2000)

(untitled) - Richter, B.; de Wolf, E.; van Koten, G.; Deelman, B.-J. (J. Org. Chem., 2000)

(untitled) - de Wolf, E.; Riccomagno, E.; de Pater, J. J. M.; Deelman, B.-J.; van Koten, G. (J. Comb. Chem., 2004)

(untitled) - Corrêa da Costa, R.; Hampel, F.; Gladysz, J. A. (Polyhedron, 2007)

(untitled) - Tuba, R.; Brothers, E. N.; Reibenspies, J. H.; Bazzi, H. S.; Gladysz, J. A. (Inorg. Chem., 2012)

(untitled) - Quarti, C.; Milani, A.; Castiglioni, C. (J. Phys. Chem. B, 2013)

(untitled) - Cormanich, R. A.; O'Hagan, D.; Bühl, M. (Angew. Chem., Int. Ed., 2017)

(untitled) - White, H. F. (Anal. Chem., 1966)

(untitled) - Foris, A. (Magn. Reson. Chem., 2004)

APEX2. Program for Data Collection on Area Detectors (BRUKER AXS Inc.)

SADABS, Program for Absorption Correction of Area Detector Frames (Sheldrick, G. M. BRUKER AXS Inc.)

(untitled) - Sheldrick, G. M. (Acta Crystallogr., Sect. A: Found. Crystallogr., 2008)

(untitled) - Sheldrick, G. M. (Acta Crystallogr., Sect. C: Struct. Chem., 2015)

(untitled) - Dolomanov, O. V.; Bourhis, L. J.; Gildea, R. J.; Howard, J. A. K.; Puschmann, H. (J. Appl. Crystallogr., 2009)

Gaussian 09, Revision D.01 (Gaussian, Inc., 2009)

(untitled) - Becke, A. D. (Phys. Rev. A, 1988)

(untitled) - Becke, A. D. (J. Chem. Phys., 1993)

(untitled) - Lee, C.; Yang, W.; Parr, R. G. (Phys. Rev. B, 1988)

(untitled) - Hariharan, P. C.; Pople, J. A. (Theor. Chim. Acta, 1973)

(untitled) - Peterson, K. A.; Shepler, B. C.; Figgen, D.; Stoll, H. (J. Phys. Chem. A, 2006)

(untitled) - Macrae, C. F.; Bruno, I. J.; Chisholm, J. A.; Edgington, P. R.; McCabe, P.; Pidcock, E.; Rodriguez-Monge, L.; Taylor, R.; van de Streek, J.; Wood, P. A. (J. Appl. Crystallogr., 2008)

(untitled) - Lichtenberger, D. L.; Gladysz, J. A. (Organometallics, 2014)